Comparative Analysis of Sharia Stock Price Indices in Indonesia, Turkey, China, and Malaysia: A Study of Integration in Sharia Capital Markets - Candra Saputra, Deky; Hamidi, Ichsan; Syathiri, Ahmad (Universitas Nahdlatul Ulama Surabaya, 2023)
The main objective of this research is to determine the long-term and short-term impacts of the relationship between the Dow Jones Islamic Market Turkey Index (DJIMTR), Dow Jones Islamic Market China/Hong Kong, Titans 30 Index (DJICHK), and Dow Jones Islamic World Malaysia Titans Index 25 (DJMY25) against the Indonesian Sharia Stock Index (JKISSI). The research method used is the Vector Error Correction Model (VECM) with Eviews 10 as an analysis tool. The data used is time series data, namely monthly data from January 2016 to May 2022 obtained from the investing.com and finance.yahoo.com websites. The study results show that in the short term, none of the independent variables have a significant impact on JKISSI. However, in the long term, DJIMTR and DJICHK show a significant negative influence on JKISSI, while DJMY25 has a significant positive influence on JKISSI. The need for policies that strengthen the integration of Islamic capital markets in the long term to strengthen economic stability and growth in related countries and encourage more research to understand the dynamics of Islamic capital markets and identify important factors that influence their performance. This research is expected to provide a better understanding of long-term and short-term relationships in Islamic capital markets in Indonesia, Turkey, China, and Malaysia.